2016
DOI: 10.1111/jce.13118
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Clinical Outcomes of Catheter Ablation of Atrial Fibrillation in Patients With Chronic Kidney Disease

Abstract: INTRODUCTION Data regarding catheter ablation of atrial fibrillation (AF) in patients with chronic kidney disease (CKD) is limited. We therefore assessed the association of CKD with common safety and clinical outcomes in a nationwide sample of ablation recipients. METHODS Using MarketScan® Commercial Claims and Medicare Supplemental Databases, we evaluated 30-day safety and 1-year clinical outcomes in patients who underwent a first AF ablation procedure between 2007–2011. We calculated frequency of common 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
0
25
3
2
Order By: Relevance
“…We identified patient baseline comorbidities using documented ICD‐9 codes in the year preceding the index ablation using algorithms and methodology described in our previous work . The principal outcome of interest was UTI within 30 days of the index AF ablation, which was ascertained by searching across all inpatient and outpatient encounters for ICD‐9 code 599.0.…”
Section: Methodsmentioning
confidence: 99%
“…We identified patient baseline comorbidities using documented ICD‐9 codes in the year preceding the index ablation using algorithms and methodology described in our previous work . The principal outcome of interest was UTI within 30 days of the index AF ablation, which was ascertained by searching across all inpatient and outpatient encounters for ICD‐9 code 599.0.…”
Section: Methodsmentioning
confidence: 99%
“…The safety and efficacy of AF ablation in CKD was evaluated in 21 091 ablations, in which 1593 cases (7.6%) had CKD and 60 were on dialysis. 112 Among patients selected for AF ablation, those with and without CKD had similar rates of post-procedural complications and subsequent AF hospitalization, DCCV, and repeat ablation, although the patients with CKD were more likely to be re-admitted for heart failure. A meta-analysis of four studies of pulmonary vein isolation using radiofrequency ablation in patients with CKD showed a nearly two-fold increased risk of AF recurrence, possibly as a result of larger pre-ablation left atrial volumes, which may serve as a marker for non-pulmonary vein triggers of AF.…”
Section: Considerations About Rhythm Controlmentioning
confidence: 93%
“…[ 4 , 5 ] In addition, atrial fibrillation may accelerate the deterioration of renal function, which can be maintained or improved by maintaining sinus rhythm. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%